Perancangan dan Pembuatan Smartfarm Menggunakan Kendali Telepon Seluler Via SMS Gateway - Kiki Fitriatma; Septian Dedi Suhendra (BEES: Bulletin of Electrical and Electronics Engineering, 2020)
The dense activity and mobility in middle and upper-middle-class society at this time resulted in many who did not have time to care for and maintain their yard. When the yard can still be used to get additional income. Where can be made hydroponic farming and fish farming? choose to use the services of gardeners rather than doing it yourself. It is something that is not efficient and effective. By creating a system of control and care for plants and fish ponds that can be controlled anywhere and anytime. This system makes it possible for each individual to carry out care and supervision only by using a cell phone so that it does not take much time. With this system many people are helped to be able to manage their yard. Not only that, but this system will also make our yard more productive because the results can be sold. So that this system can also be useful as a new business venture. The application of this system in every home yard can have an impact on the time each individual becomes more efficient, the use of cell phones to control electronic components is felt to make their use more practical and efficient.